Organizational Citizenship Behavior (OCB) Variable on Employees Of PT. Smartfren Jember - Triane Wahyu Lestari (Universitas Pendidikan Ganesha, 2018)
This study aims to examine and analyze empirically the influence of job satisfaction, organizational culture, motivation and organizational commitment to OCB on employees of PT. Smartfren Jember. This research was conducted on employees of PT. Smartfren Jember. The research population was employees of PT. Smartfren Jember numbered 120 people. The sampling technique used in this study is proportional sampling. The numbers of samples of this study were 50 people scattered in all parts of PT. Smartfren Jember. Data analysis method uses multiple linear regression. The results showed that 1) Job satisfaction had a positive effect through OCB on employees of PT. Smartfren Jember; 2) Organizational Culture has a positive effect through OCB on employees of PT. Smartfren Jember; 3) Motivation has a positive effect through OCB on employees of PT. Smartfren Jember; 4) Organizational commitment has a positive effect through OCB on employees of PT. Smartfren Jember; 5) Job satisfaction, organizational culture, motivation, organizational commitment simultaneously have a positive effect through OCB on employees of PT. Smartfren Jember